Description of tadpoles of five frog species in the subgenus Brygoomantis from Madagascar (Mantellidae: Mantidactylus) - Schmidt, Heike; Strauß, Axel; Glaw, Frank; Teschke, Meike; Vences, Miguel (Zootaxa, 2009)
We describe the larval stages of five frog species classified in the Madagascan subgenus Brygoomantis of the genus Mantidactylus, which were identified by DNA barcoding: Mantidactylus alutus, Mantidactylus curtus, and three taxonomically undescribed species here named Mantidactylus sp. aff. biporus "Ranomafana", M. sp. aff. biporus "Marojejy", and M. sp. aff. curtus "Ankaratra". The larvae of M. alutus, and of M. sp. aff. curtus "Ankaratra", had been described before, and we confirm and complement the previous studies. Our data confirm that Brygoomantis tadpoles are benthic, of a rather generalized body shape and oral disc morphology. All species for which tadpoles are known so far have a large dorsal gap of marginal papillae, a labial tooth row formula of 3-5 rows on the anterior labium of which only the first is continuous and the others have distinct medial gaps, and three rows of labial teeth on the posterior labium of which the first usually has a very small medial gap which however can sometimes be undetectable. Total number of marginal and submarginal papillae ranges from 50 to 103 and density of labial teeth (on the second upper row) from 19 to 76 per mm.